The Brief Inventory of Psychosocial Functioning (B-IPF): Ukrainian-language adaptation and psychometric evaluation - ALEKSINA, Nadiia; GERASYMENKO, Olga; LAVRYNENKO, Denys; SAVCHENKO, Olena; ZARUBIN, Ilya (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. The adaptation and psychometric evaluation of the Brief Inventory of Psychosocial Functioning (B-IPF) address the need for a quick, reliable tool to assess psychosocial impairments in the Ukrainian context. This study fills a gap in available diagnostic methods for evaluating psychosocial functioning in both clinical and research settings. Given the importance of assessing psychosocial functioning for determining mental health, the B-IPF enables the evaluation of aspects such as relationships, work, education, and self-care, which are crucial for both clinical practice and research. Methods. The primary approach was a two-phase adaptation involving forward and backward translations, expert evaluation, and testing on a sample (N=786) in the first phase and (N=315) in the second phase. Results. The results of the reliability assessment demonstrated that the Brief Inventory of Psychosocial Functioning in the Ukrainian sample showed high reliability scores according to Cronbach’s alpha and McDonald’s omega. An exploratory factor analysis revealed a two-factor structure, where the first factor reflects functioning issues in a broad context (friendship, work, education, and self-care), and the second factor relates to a close context (romantic relationships, parenting, and family). The results also demonstrated a high degree of model fit in the confirmatory factor analysis for both the structure identified in the exploratory factor analysis (RMSEA = 0.028, CFI = 0.995, TLI = 0.992) and when testing the original structure (RMSEA = 0.074, CFI = 0.960, TLI = 0.940). The evaluation of convergent validity indicated that the adapted questionnaire shows significant correlations with related constructs. The B-IPF also demonstrated a high level of stability in results over time. Conclusions. The findings support the B-IPF as a reliable tool for assessing psychosocial impairments. However, further research with a more diverse sample is needed to enhance the validity of broader results and establish testing norms.